2020
DOI: 10.3389/fimmu.2020.595877
|View full text |Cite
|
Sign up to set email alerts
|

Gene Networks Underlying the Resistance of Bifidobacterium longum to Inflammatory Factors

Abstract: As permanent residents of the normal gut microbiota, bifidobacteria have evolved to adapt to the host’s immune response whose priority is to eliminate pathogenic agents. The mechanisms that ensure the survival of commensals during inflammation and maintain the stability of the core component of the normal gut microbiota in such conditions remain poorly understood. We propose a new in vitro approach to study the mechanisms of resistance to immune response factors based on high-throughput … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…433 It has been shown that bifidobacteria, in particular Bifidobacterium longum GT-15, can reduce intestinal inflammatory processes by producing the type-III fibronectin domain-containing protein (FN3) that binds to a pro-inflammatory agent such as tumor necrosis factor α TNFα. 434,435 The gut microbiome of people resistant to coronavirus infection is a promising source of Lactobacillus strains capable of producing peptides and other active metabolites that prevent the penetration of COVID-19 into human cells and decrease the severity and pathogenesis of this new coronavirus.…”
mentioning
confidence: 99%
“…433 It has been shown that bifidobacteria, in particular Bifidobacterium longum GT-15, can reduce intestinal inflammatory processes by producing the type-III fibronectin domain-containing protein (FN3) that binds to a pro-inflammatory agent such as tumor necrosis factor α TNFα. 434,435 The gut microbiome of people resistant to coronavirus infection is a promising source of Lactobacillus strains capable of producing peptides and other active metabolites that prevent the penetration of COVID-19 into human cells and decrease the severity and pathogenesis of this new coronavirus.…”
mentioning
confidence: 99%
“…It has been presumed that other species of bifidobacteria sustain cytokine homeostasis in the enteric immune system by binding other cytokines such as IL-6 and IL-beta. A recent study demonstrated how increasing concentration of TNF-α in the growth medium affects gene expression in bifidobacteria [89].…”
Section: Binding Of the Fn3 Protein Fragment To Cytokines (Tnf-α)mentioning
confidence: 99%
“…Using whole transcriptome analysis, the authors demonstrated that supplementation of B. longum GT15 culture medium with high concentration of the pro-inflammatory cytokine TNF-α (10 ng/mL) altered the expression of 1000 genes and 176 operons [89]. Many of the genes whose expression was significantly increased, among which was fn3, encoded proteins with antioxidant activity such as heat shock protein (hsp20) [90], glutathione [91], ABC transporters [92], enzymes involved in the metabolism of amino acids such as leucine, arginine [87], and short-chain fatty acids including propionate [93].…”
Section: Binding Of the Fn3 Protein Fragment To Cytokines (Tnf-α)mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of this gene (as well as other genes of the PFNA operon) increased as the strain B. longum subsp. longum GT15 was grown in the presence of TNFα [5]. The FN3 protein is found in most bifidobacteria and it contains a signal peptide, a transmembrane domain, and two FN3 domains [1][2][3][4].…”
mentioning
confidence: 99%